Surgical treatment of a vertebral fracture associated with a haematogenous osteomyelitis in a dog - Cabassu, J.; Moissonnier, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
A seven-month-old Rottweiler was referred for a diagnosed femoral neck fracture and a suspected vertebral fracture. The simplified neurological examination revealed an acute paraplegia. A discospondyilitis associated with a pathologic fracture of Th11 and a spinal compression, and a haematogenous epiphysitis of the femoral neck were diagnosed based on radiographic and computed tomographic examinations. The vertebral fracture was stabilised using screws and polymethylmetacrylate with gentamycin by a lateral intercostal approach. The dog was able to walk seven days later. A femoral head and neck ostectomy was performed two weeks later. Staphylococcus intermedius was isolated from both sites, which confirmed the diagnosis. The dog was treated with cephalexin (30 mg/kg/d) for six weeks. A telephone interview with owners indicated that no more clinical signs were present four months after the second surgery. Discospondylitis associated with haematogenous osteomyelitis has only been reported in two cases. Paraplegia is an unusual clinical presentation for discospondylitis. The lateral approach (which allowed a direct access to the infected site) and the technique (screws associated with antibiotic-impregnated cement) are unique for surgical treatment of discospondylitis. Although applying cement to an infected area may pose a risk, antibiotic-loaded cement is successfully used in the treatment of chronic osteomyelitis in humans.
Keywords: Discospondylitis; neurosurgery; staphylococcus; osteomyelitis